Chronic Mild Stress Modulates Activity-Dependent Transcription of BDNF in Rat Hippocampal Slices. (31st December 2015) - Molteni, Raffaella; Rossetti, Andrea C.; Savino, Elisa; Racagni, Giorgio; Calabrese, Francesca
Abstract : Although activity-dependent transcription represents a crucial mechanism for long-lasting experience-dependent changes in the hippocampus, limited data exist on its contribution to pathological conditions. We aim to investigate the influence of chronic stress on the activity-dependent transcription of brain-derived neurotrophic factor (BDNF). The ex vivo methodology of acute stimulation of hippocampal slices obtained from rats exposed to chronic mild stress (CMS) was used to evaluate whether the adverse experience may alter activity-dependent BDNF gene expression. CMS reduces BDNF expression and that acute depolarization significantly upregulates total BDNF mRNA levels only in control animals, showing that CMS exposure may alter BDNF transcription under basal conditions and during neuronal activation. Moreover, while the basal effect of CMS on total BDNF reflects parallel modulations of all the transcripts examined, isoform-specific changes were found after depolarization. This different effect was also observed in the activation of intracellular signaling pathways related to the neurotrophin. In conclusion, our study discloses a functional alteration of BDNF transcription as a consequence of stress. Being the activity-regulated transcription a critical process in synaptic and neuronal plasticity, the different regulation of individual BDNF promoters may contribute to long-lasting changes, which are fundamental for the vulnerability of the hippocampus to stress-related diseases.